An Artist within, brings out the Drawing in Class: A Creative Approach to Teaching and Learning Engineering Graphics and Design - Siphesihle Eugene Mthethwa (E-Journal of Humanities, Arts and Social Sciences)
Allowing Engineering Graphics and Designs (EGD) learners to express themselves with music in the EGD class is part of what makes the lesson worth having. Validating learners to sing their hearts out during the lesson allows them to be willing to work on and complete their assigned EGD activities, love the subject, and long for the next lesson. This study therefore aimed to explore how an infusion of music in EGD lessons would impact teaching and learning of EGD. Some scholarly findings show that music can deeply provoke emotions, influence mood and affect cognitive performance. A qualitative approach was adopted and a purposive sampling technique where 13 grade 11 and 12 technical students doing EGD were sampled and music was infused during their EGD period. Data generated was collected using structured interviews and classroom observations. Thematically, data was analysed and responses were themed, compared, and contrasted to shed light on a creative approach to EGD and how it can enhance the teaching and learning of EGD. This study found that allowing learners to sing does give them a sense of ease and they become comfortable around the teacher. It relaxes their minds and enhances their performance. The study recommends that although the results have been positive, it also depends on the style of teaching that one uses and is comfortable to use. This study contributes towards creating enabling learning environment for EGD learners.